Mińkowce: Podolski «Hamlet» i święto dożynek - Jarosław Komorowski (Pamiętnik Teatralny, 2017)
Mińkowce, a town in the far-away Podolia, became a part of history of the Polish theater as the place where the first Polish edition of Shakespeare’s Hamlet, as translated by Jan Nepomucen Kamieński based on Friedrich Ludwig Schröder’s adaptation, was published in 1805. Since 1790, Mińkowice, along with an expansive landed estate of 20 villages, had been owned by Ignacy Ścibor Marchocki. The estate owner chose not to acknowledge the partitions of Poland and established his own “Mińkowice state” sometime after 1795, strongly emphasising its independence from the Russian Empire; he even set up his own boundary markers. He released his peasants from the bond of personal serfdom and laid down laws in the spirit of the Enlightenment; he founded a school, printer, and “music academy.” At the same time, Marchocki flaunted his power and role of “the protector of the people” with extravagant ceremonies, which earned him the reputation of an eccentric or even madman. In reality, just like in Hamlet’s case, it was probably Marchocki’s way of concealing his real intentions from Russian civil officers and neighbours disapproving of social reform. Marchocki established two “state” holidays in his landed estate, the New Year and harvest festival, which was held on 15 August, on the Feast of St Mary the Virgin. The latter was a religious feast combined with a grand, all-day-long spectacle put on by Marchocki for 30 consecutive years according to an increasingly complex and theatrical scenario. As years went by, the basic scheme (a procession after the Mass, a feast in front of an outdoor altar, symbolic ploughing, an apotheosis of the goddess of harvest) became more and more elaborate. Pieces of occasional architecture and stage set, special costumes, and props appeared. A tribute to a personified goddess of harvest was the final and part of the feast. Eyewitnesses started calling the personified goddess by the Roman name of Ceres, which brought onto Marchocki absurd accusations of paganism and idolatry, which, however, did not make him budge, as he kept organising the unusual celebrations until the end of his life.